Toxicity of Cadmium (Cd) on Artemia salina - Dyonisius Hutauruk; Yusni Ikhwan Siregar; Irvina Nurrachmi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Cd is a non-essential metal and a widespread micropollutant that has physiological effects on aquatic organisms. Cd heavy metal poisoning can be acutely caused by contamination at high doses, while chronic poisoning is generally caused by low levels of contamination and long exposure time. This research was conducted in June 2022 at the Marine Chemistry Laboratory Faculty of Fisheries and Marine, Universitas Riau, which aims to determine the value of LC50 (Lethal Concentration) for 24 hours after being given a toxicant in the form of Cd and to determine the level of Cd toxicity in A. salina. The method used in this research is the experimental method with the experimental unit A. salina. The LC50 of Cd on A. salina revealed 11.7109 mg/L. This concentration is capable of causing the death of 50% of the test animals. Furthermore, the water quality in the acute toxicity test, P0 (control), was classified as good to support the life of A. salina, while at P1 (3.13 mg/L) - P5 (50 mg/L), it was classified as polluted